PTK 7 is a transforming gene and prognostic marker for breast cancer and nodal metastasis involvement. - Silvia Gärtner; Angela Gunesch; Tatiana Knyazeva; Petra Wolf; Bernhard Högel; Wolfgang Eiermann; Axel Ullrich; Pjotr Knyazev; Beyhan Ataseven (PLoS ONE, 2014)
Protein Tyrosin Kinase 7 (PTK7) is upregulated in several human cancers; however, its clinical implication in breast cancer (BC) and lymph node (LN) is still unclear. In order to investigate the function of PTK7 in mediating BC cell motility and invasivity, PTK7 expression in BC cell lines was determined. PTK7 signaling in highly invasive breast cancer cells was inhibited by a dominant-negative PTK7 mutant, an antibody against the extracellular domain of PTK7, and siRNA knockdown of PTK7. This resulted in decreased motility and invasivity of BC cells. We further examined PTK7 expression in BC and LN tissue of 128 BC patients by RT-PCR and its correlation with BC related genes like HER2, HER3, PAI1, MMP1, K19, and CD44. Expression profiling in BC cell lines and primary tumors showed association of PTK7 with ER/PR/HER2-negative (TNBC-triple negative BC) cancer. Oncomine data analysis confirmed this observation and classified PTK7 in a cluster with genes associated with agressive behavior of primary BC. Furthermore PTK7 expression was significantly different with respect to tumor size (ANOVA, p = 0.033) in BC and nodal involvement (ANOVA, p = 0.007) in LN. PTK7 expression in metastatic LN was related to shorter DFS (Cox Regression, p = 0.041). Our observations confirmed the transforming potential of PTK7, as well as its involvement in motility and invasivity of BC cells. PTK7 is highly expressed in TNBC cell lines. It represents a novel prognostic marker for BC patients and has potential therapeutic significance.